2021
DOI: 10.1590/1678-992x-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Like Kinase (RLK) as a candidate gene conferring resistance to Hemileia vastatrix in coffee

Abstract: The biotrophic fungus Hemileia vastatrix causes coffee leaf rust (CLR), one of the most devastating diseases in Coffea arabica. Coffee, like other plants, has developed effective mechanisms to recognize and respond to infections caused by pathogens. Plant resistance gene analogs (RGAs) have been identified in certain plants as candidates for resistance (R) genes or membrane receptors that activate the R genes. The RGAs identified in different plants possess conserved domains that play specific roles in the fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Plant perception of the pathogen invasion follows a surveillance system assembled in a multilayer fashion to identify apoplastic and cytoplasmatic pathogen effectors. At the early stages of the infection process, some of the multi-domain recognition receptors are activated in the incompatible coffee-H. vastatrix interaction (RLK and LRR-RLK2, NBS-LRR), suggesting their role in the host resistance response [22,140,150,152,153]. Nevertheless, in some other incompatible coffee-H. vastatrix interactions, this may not be the case [143,152], indicating that immune receptors can have different mechanisms for ligand binding and receptor complex formation, which can modulate the activation, intensity and duration of plant immune responses [162].…”
Section: Genementioning
confidence: 99%
See 1 more Smart Citation
“…Plant perception of the pathogen invasion follows a surveillance system assembled in a multilayer fashion to identify apoplastic and cytoplasmatic pathogen effectors. At the early stages of the infection process, some of the multi-domain recognition receptors are activated in the incompatible coffee-H. vastatrix interaction (RLK and LRR-RLK2, NBS-LRR), suggesting their role in the host resistance response [22,140,150,152,153]. Nevertheless, in some other incompatible coffee-H. vastatrix interactions, this may not be the case [143,152], indicating that immune receptors can have different mechanisms for ligand binding and receptor complex formation, which can modulate the activation, intensity and duration of plant immune responses [162].…”
Section: Genementioning
confidence: 99%
“…Coffee-H. vastatrix interactions are governed by the Flor's gene-for-gene relationship, and the resistance of coffee plants is conditioned at least by nine major dominant genes (S H 1-S H 9) singly or associated [11,19,20], although other major and minor genes may also be involved [11,21,22]. The use of coffee-resistant varieties is considered the most sustainable, efficient, and eco-friendly strategy to control this disease.…”
Section: Introductionmentioning
confidence: 99%
“…vastatrix in stomata of coffee leaves, both in resistant and susceptible genotypes and at 48 hpi the presence of haustoria is already observed [ 75 77 ]. In addition, a LRR receptor-like kinase described in this pathosystem has a peak expression at 24 hpi in compatible and incompatible interactions [ 78 ], thus suggesting that the signal exchange between the two organisms is already occurring in this period.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments showed that at 24 hpi it is already possible to detect the penetration of the hypha produced by the appressorium of H. vastatrix in stomata of coffee leaves, both in resistant and susceptible genotypes and at 48 hpi the presence of haustoria is already observed [7678]. In addition, a LRR receptor-like kinase described in this pathosystem has a peak expression at 24 hpi in compatible and incompatible interactions [79], thus suggesting that the signal exchange between the two organisms is already occurring in this period.…”
Section: Discussionmentioning
confidence: 99%